New Word Formations in J.K. Rowling's Fantastic Beasts and Where to Find Them Film - Walid, Ahmad Nafiul; Natsir, Muhammad; Sanhadi Rahayu, Famala Eka (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research investigated types of word formation process found in J.K. Rowling’s Fantastic Beast and Where to Find Them film using Yule’s theory (2010). The methodology was descriptive qualitative research because it focused on words as its data produced in Fantastic Beast and Where to Find Them film and the data was explicated descriptively. The analysis revealed that the processes of word-formation of new words in Fantastic Beast and Where to Find Them film consist of borrowing, compounding, blending, acronym, and multiple processes. From the findings, it can be implied that borrowing was the most frequent process that occurred in Fantastic Beast and Where to Find Them film. The new words found in Fantastic Beasts and Where to Find Them film have the functions as naming beasts, magic spells, and describing person or building.